2020
DOI: 10.1186/s12864-020-6479-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the NAC transcription factor family in broomcorn millet (Panicum miliaceum L.) and expression analysis under drought stress

Abstract: Background: Broomcorn millet is a drought-tolerant cereal that is widely cultivated in the semiarid regions of Asia, Europe, and other continents; however, the mechanisms underlying its drought-tolerance are poorly understood. The NAM, ATAF1/2, and CUC2 (NAC) transcription factors form a large plant-specific gene family that is involved in the regulation of tissue development and abiotic stress. To date, NAC transcription factors have not been systematically researched in broomcorn millet.Results: In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 69 publications
(91 reference statements)
3
19
0
Order By: Relevance
“…In this study, the tissue-specific expression pattern showed that more than 40 DgNAC genes exhibited higher expression in roots than other detected orchardgrass tissues, such as DgNAC008/052/026/023/034/061/045 . Similar results were also found in other plants, such as Fagopyrum tataricum [ 46 ], Panicum miliaceum [ 47 ] and Triticum aestivum [ 62 ]. DgNAC046, DgNAC087, and DgNAC103 exhibited higher expression than the other genes in the stems of orchardgrass, and they may play an important role in stem development.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, the tissue-specific expression pattern showed that more than 40 DgNAC genes exhibited higher expression in roots than other detected orchardgrass tissues, such as DgNAC008/052/026/023/034/061/045 . Similar results were also found in other plants, such as Fagopyrum tataricum [ 46 ], Panicum miliaceum [ 47 ] and Triticum aestivum [ 62 ]. DgNAC046, DgNAC087, and DgNAC103 exhibited higher expression than the other genes in the stems of orchardgrass, and they may play an important role in stem development.…”
Section: Discussionsupporting
confidence: 85%
“…According to the sequence homology with Arabidopsis , all 108 DgNAC genes were divided into 13 subgroups [ 13 ]. The results were inconsistent with other species, such as Fagopyrum tataricum (15 subgroups) [ 46 ], Capsicum annuum (14 subgroups) [ 52 ] and Capsicum annuum (12 subgroups) [ 47 ], suggesting that NAC proteins exhibit diversity in various species. The results of conserved motif analysis of orchardgrass NAC proteins further confirm the classification of the DgNAC family.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Transformed yeast cells expressing OsNAM and OsGRAM showed enhanced tolerance under osmotic stress; moreover, the transformed cells were able to survive at relatively high temperatures, and they displayed increase tolerance to arsenite and arsenate. OsNAM belongs to the NAC family of TFs, which is a large plant-specific gene family that is related to the regulation of tissue development and the response to abiotic stress ( Shan et al, 2020 ). OsGRAM is important for the ABA response, hormone signaling under stress conditions, and the perception of environmental stimuli and regulation of the response to those stimuli ( Mauri et al, 2016 ).…”
Section: Beneficial Bacteriamentioning
confidence: 99%
“…NAC13 appears to be an important gene to mediate diverse stress responses in plants. NAC13 expression is induced by UV-B in Arabidopsis independently of the UVR8 photoreceptor (O’Hara et al, 2019) and is also induced by salt stress in poplar (Zhang et al, 2019), and by drought in broomcorn millet (Shan et al, 2020). In our study, however, drought on its own did not induce NAC13 expression in tobacco (Fig.…”
Section: Discussionmentioning
confidence: 99%